(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This article examines the representation of indigenous peoples in Chilean comics published between 1998 and 2023, analyzing 57 identified titles. The study reveals a significant increase in the production and diversification of these narratives, coinciding with sociopolitical changes in Chile that have reconfigured the relationships between the state and indigenous peoples. A predominance of representations of the Mapuche people (59.6%) is observed, followed by the Selk’nam (19.3%) and Rapa Nui (8.8%). The analysis covers format, temporality, target audience, and genre, evidencing a trend toward more complex and multidimensional narratives. This new scenario of comic production is critically discussed as a space for cultural negotiation, identity construction, and the articulation of alternative narratives.